Quality of Life of Children with Thalassemia in Indonesia: Review - Rahmah Rahmah; Sri Nabawiyati Nurul Makiyah (Universitas Muhammadiyah Yogyakarta, 2022)
Background: Thalassemia is an inherited disorder of hemoglobin (Hb) synthesis. Treatment of thalassemia has not yet reached the level of cure. Globally, the management of thalassemia is symptomatic in the form of lifelong blood transfusions. Data on children with thalassemia major in Indonesia has not been widely published. However, various studies clearly showed growth and development disorders and behavior that greatly affected the quality of life of children with thalassemia. Blood transfusions and lifelong use of drugs often lead to feelings of boredom of treatment, not to mention physical changes and the feeling of being different from relatives or friends that will cause the feeling of inferiority. They often drop out of school and do not find work, which causes highly severe psychosocial effects. Objective: This paper aims to provide an overview of the quality of life of children with thalassemia in Indonesia so that it can be used as a reference in providing appropriate management regarding the quality of life of children with thalassemia. Methods: This literature search used google scholar and pubmed for complete publications in 2010-2020 with the keywords